Answer :
Answer:
Jake's error in step 3
Step-by-step explanation:
we have
[tex]x^{2} -6x+5=0[/tex]
Complete the square
step 1
Group terms that contain the same variable, and move the constant to the opposite side of the equation
[tex]x^{2} -6x=-5[/tex]
step 2
Complete the square. Remember to balance the equation by adding the same constants to each side
[tex]x^{2} -6x+9=-5+9[/tex]
[tex]x^{2} -6x+9=4[/tex]
step 3
Rewrite as perfect squares
[tex](x-3)^{2}=4[/tex]
Jake's error in step 3
He placed 6 instead of 3 in the left side
step 4
take square root both sides
[tex]\sqrt{(x-3)^2} =\sqrt{4}[/tex]
step 5
[tex](x-3)=\pm2[/tex]
step 6
[tex]x=3\pm2[/tex]
step 7
x=5 and x=1